Synovial Immunohistological Biomarkers of the Classification of Undifferentiated Arthritis Evolving to Rheumatoid or Psoriatic Arthritis - Cuervo, Andrea; Celis, Raquel; Julià, Antonio; Usategui, Alicia; Faré, Regina; Ramírez, Julio; Azuaga, Ana Belen; Lorenzo, Andrés; Sanmartí, Raimon; Pablos, José L.; Cañete, Juan D. (Frontiers in Medicine, 2021)
Background: Undifferentiated arthritis (UA) is defined as an inflammatory arthritis that does not fulfill criteria for a definite diagnosis. Delay in reaching a specific diagnostic and therapy may lead to impaired functional outcomes. Our aim was to identify synovial biomarkers associated with definitive diagnostic classification in patients with UA. Methods: DMARD-naïve UA patients with available initial synovial tissue (ST) and a final diagnosis of rheumatoid arthritis (RA) or psoriatic arthritis (PsA) during follow-up were included and compared with patients with well-defined disease (RA or PsA). Clinical, arthroscopic, and pathological data were compared between groups. Pathology included quantitative immunohistochemical (IHC) analysis of cell types and human interferon-regulated MxA. Principal component analysis (PCA) was performed to extract disease patterns. Results: 105 patients were included: 31 patients with DMARD-naïve UA (19 evolving to RA and 12 to PsA during a median follow up of 7 years), 39 with established RA, and 35 with established PsA. ST from the UA group showed higher macrophage density compared with the established RA and PsA groups. Patients with UA evolving to RA (UA-RA) showed higher MxA expression and CD3+ T-cell density compared with established RA. UA patients evolving to PsA (UA-PsA) showed increased vascularity and lining synovial fibroblast density compared with established PsA. Synovitis of UA-PsA patients showed more mast cells and lining fibroblasts compared with UA-RA. No between-group differences in local or systemic inflammation markers were found. Conclusions: Our results show differences in the cellular composition of UA synovium compared with RA and PsA, with higher density of the cellular infiltrate in the UA groups. Initial expression of the interferon inducible gene MxA could be a biomarker of progression to RA, while higher mast cell and fibroblastic density may be associated with PsA progression.